2011
DOI: 10.1001/archsurg.2011.32
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Surgeon Experience on 5-Year Outcome of Laparoscopic Nissen Fundoplication

Abstract: To investigate the 5-year effect of surgeon experience with laparoscopic Nissen fundoplication (LNF). In 2000, a randomized controlled trial (RCT) was prematurely terminated because LNF for gastroesophageal reflux disease was associated with a higher risk to develop dysphagia than conventional Nissen fundoplication (CNF). Criticism focused on alleged bias caused by the relative lack of experience with the laparoscopic approach of the participating surgeons.Design: Multicenter RCT and prospective cohort study.S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 37 publications
2
12
1
Order By: Relevance
“…Several studies have shown surgical outcomes to be dependent on operator experience. 47 52 Although questions have been raised about operator use, quality of the mastectomy skin flaps, and surgical outcomes in breast reconstruction, our study found no association between skin necrosis and the type of mastectomy performed or between necrosis and the attending surgical oncologist or reconstructive surgeon placing and filling the TE (data not shown). Further, there was no association between placement of acelluar dermal matrix and necrosis.…”
Section: Discussioncontrasting
confidence: 51%
“…Several studies have shown surgical outcomes to be dependent on operator experience. 47 52 Although questions have been raised about operator use, quality of the mastectomy skin flaps, and surgical outcomes in breast reconstruction, our study found no association between skin necrosis and the type of mastectomy performed or between necrosis and the attending surgical oncologist or reconstructive surgeon placing and filling the TE (data not shown). Further, there was no association between placement of acelluar dermal matrix and necrosis.…”
Section: Discussioncontrasting
confidence: 51%
“…On the other hand, clinical outcomes of symptom resolution and patient satisfaction do not improve with experience [1819]. Consistently, we did not observe a difference in symptomatic outcomes according to surgeon experience.…”
Section: Discussionsupporting
confidence: 78%
“…In all patients a standardised, floppy 360° LNF of 2.5–3.0 cm was constructed after ligation and division of the short gastric vessels, full mobilisation of the oesophagus and posterior crural repair 31–33. LNF was performed by two surgeons beyond the learning curve for LNF,34 either at the University Medical Center Utrecht (EJH and IAMJB) or the tertiary teaching hospital; Meander Medical Center (IAMJB).…”
Section: Methodsmentioning
confidence: 99%